Overexpression of ADAM9 decreases radiosensitivity of hepatocellular carcinoma cell by activating autophagy. Issue 1 (1st January 2021) - Zhu, Lijin; Zhao, Yuanyuan; Yu, Li; He, Xinjia; Wang, Yingju; Jiang, Peng; Yu, Rong; Li, Wei; Dong, Bin; Wang, Xiang; Dong, Yinying
ABSTRACT: A disintegrin and a metalloprotease (ADAM)9 upregulated within human hepatocellular carcinoma (HCC) cells, but its effect on HCC radiosensitivity remains unknown. The present work aimed to examine the effect of ADAM9 on HCC radiosensitivity and to reveal its possible mechanism, which may be helpful in identifying a potential therapeutic strategy. Changes in ADAM9 expression after X-ray irradiation were identified using western blot, qRT-PCR, and immunofluorescence. ADAM9 stable knockdown and overexpression cell lines were constructed using lentivirus packaging. The radiosensitivity of HCC cells with altered ADAM9 expression was examined by CCK-8 assays, subcutaneous tumorigenesis experiments, and clone formation assays. This study also determined how autophagy affected HCC cell radiosensitivity. Furthermore, ADAM9, p62 and Bax expressions in HCC tissues that were removed after radiotherapy were detected by immunohistochemistry, and the relationship among the levels of these molecules was statistically analyzed. The level of ADAM9expression in HCC cells increased after X-ray irradiation. Through CCK-8 assays, subcutaneous tumorigenesis experiments, and clone formation assays, this work discovered the increased MHCC97H cell radiosensitivity after ADAM9 knockdown, and the radiosensitivity of Huh7 cells decreased after the overexpression of ADAM9. Furthermore, ADAM9 induced HCC cell autophagy via downregulating Nrf2 expression, while autophagy inhibition or induction reversed the effects of altered ADAM9 expression on radiosensitivity. Moreover, ADAM9 level showed a negative correlation with Bax and p62 expression within HCC tissues after radiotherapy. Taken together, ADAM9 decreased the radiosensitivity of HCC cells, and autophagy mediated this process.